“INTEGRITY, DISCIPLINE AND HUMBLE, CONSTANT HARD WORK – THESE ARE THE SECRETS OF A LONG AND SUCCESSFUL CAREER” - Adél FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
Júlia Kirkósa was born in 1947 in Gherla, Romania. After graduating from the “Gh. Dima” Music Academy in Cluj, in 1973 she became the lead singer of the Hungarian Opera from Cluj-Napoca. Throughout her career, she performed many prima donna roles (such as Saffi in The Gypsy Baron by Johann Strauss II, Countess Liza in The Land of Smiles by Franz Lehár, Rosalinda in Die Fledermaus, Victoria etc.) and has achieved well-deserved recognition for her interpretation of Verdi’s heroines – Abigaille, in Nabucco, Leonora in Il Trovatore, Amelia in Un Ballo in Maschera, Amerlia Grimaldi in Simon Boccanegra as well as Lady Macbeth, but also for the roles of Micaëla (from Carmen by Georges Bizet), Santuzza (from Cavaleria Rusticana by Pietro Mascagni), Elisabeth (in Wagner’s Tannhäuser) or Puccini’s Tosca. Her talent was acknowledged both in Romania and abroad. Júlia Kirkósa has performed in Hungary, The Netherlands, England, Italy, Bulgaria etc., and has had the opportunity to work with famous opera directors, such as Hero Lupescu or Kürthy András. Following a very successful gala concert held in the honor of soprano Júlia Kirkósa – in which she herself also performed – we sat down to discuss her career and her life experiences both as an artist and a teacher.